EXPLORATION OF AGENT-BASED SIMULATION: THE MULTIPLIER EFFECT OF ZAKAH ON ECONOMIC GROWTH - Diyah Putriani; Gairuzazmi Mat Ghani; Mira Kartiwi (Bank Indonesia, 2020)
Zakat plays an undeniably significant role in social life. The enforcement of zakah in early Islamic history is evidence that it is a powerful tool for fostering economic growth. The economy under the reign of Caliphate Umar Ibn Abdul Azis even achieved a surplus, with no one having the right to receive zakah. Recent studies have attempted to link the role of zakah and economic growth qualitatively by arguing that zakah can contribute to economic development. However, the extent to which it has a multiplier effect on economic growth has not been examined. Considering this research gap, this study examines such an effect on economic growth, as represented by Gross Domestic Product (GDP). To capture the full impact of zakah on aggregate production, two scenarios are conducted, namely the economy with and without zakah. The simulation results show that zakah can promote aggregate production. On the other hand, the economy experiences lower aggregate production when there is no zakah. An agent-based computational model (ABM) simulation is employed to run the simulation. The application of ABM in this study is intended to introduce the use of computational study as an alternative method of developing research in Islamic economics.